COMPARISON OF THE ANTITUMOR EFFECT OF KOLHIPRIT-NEO WITH THE EFFECT OF COMMERCIAL DRUGS - Makhmudovna Urozov, Enikeeva Zulfiya; Nuriddin Elmuratovich; Agzamova Nigora Alimukhamedovna; Ibragimov Shavkat Narzikulovich; Shakhanova Shakhnoza Shavkatovna (PT. Antis International Publisher, 2024)
Objective: In this study, mice with transplanted Sarcoma 180 and Solid Ehrlich tumors (SET) were used to test the antitumor activity of oral K-20 (colchiprit-neo) against different cytostatics. Methods: Antitumor activity was tested in outbred mice with transplanted tumors, treated orally with K-20 and XELODA, and intraperitoneally with doxorubicin, taxol, etoposide, or other cytostatics. Treatment was began on the 4th-5th day post-transplantation, delivered daily for 10 days. Tumor growth inhibition (TGI), animal body and spleen weight, and hematopoietic indices were measured, with statistical significance set at p < 0.05. Results: While other treatments showed significant reductions in hematopoietic parameters, K-20 treatment did not significantly affect body or spleen weight or leukocyte levels. K-20 showed superior antitumor activity, inhibiting tumor growth by 92-94% in Sarcoma 180 and SET models, outperforming doxorubicin (90%) and taxol (84-88%), and demonstrating 27% greater efficacy than XELODA. Novelty: In contrast to conventional cytostatics, K-20's oral administration demonstrated strong anticancer effects along with a good safety record and little influence on hematopoiesis or organ weights.